Encapsulation of a Novel Enterococcus faecalis Bacteriophage into Chitosan-alginate Microspheres as a Delivery System to Prevent Oral Diseases - Sonia Bhonchal Bhardwaj; Sanjay Chhibber; Shaveta Sood; Manjula Mehta; Jyoti Sharma (Journal of Global Infectious Diseases)
Introduction: Enterococcus faecalis is a Gram-positive facultative anaerobe bacteria now known to be implicated in periodontitis, tooth root infections, adimplantitis which are oral biofilm-mediated diseases. The ability of E. faecalis to form a biofilm even as a mono-infection makes it more resistant to antibiotics. Bacteriophages are known to cure antibiotic-resistant bacterial infections. However, the main concern in phage formulations is the bacteriophage stability and loss of “antibacterial” activity. Methods: In this study, a novel E. faecalis phage was isolated against E. faecalis 29212 from the sewage sample. The phage was propagated and identified using transmission electron microscope. Encapsulated phages were prepared using a biodegradable food grade chitosan-alginate coating shell suspended in honey-gelatin. The morphology of the chitosan-alginate microsphere was examined using scanning electron microscope (SEM) and pore size was determined by field emission gun-SEM. The encapsulated phages were checked for their lytic activity against host bacteria. The encapsulated bacteriophage was assayed for acid stability and thermal stability in simulated saliva. Results: The phage isolated was lytic belonging to Siphoviridae family. The mean diameter of the chitosan-alginate microspheres was 1.7 ± 0.13 mm. The pore size of the phage-loaded chitosan-alginate shell was less than 100 nm, resulting in sustained release of the phages. The chitosan-alginate encapsulated phage was stable for a long time (6 h) in simulated saliva. The encapsulated phage could withstand exposure to different pH (pH 2, pH 4, and pH 7) in simulated saliva. It was also stable at different temperatures (4°C, 37°C, and 60°C). Conclusion: The encapsulated phage has the potential to be used as phage therapy in oral diseases. Further, the chitosan-alginate encapsulated phage microsphere can be incorporated in a patch/membrane/gel in combination with antibiotics/nutritional components/anti-inflammatory agents as treatment for oral diseases induced by E. faecalis.